Zero Trust SD-WAN: Enhancing Security and Efficiency in the Medical Industry - Venkadesan Perumal (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
Zero Trust Software-Defined Wide Area Network (SD-WAN) technology has emerged as a critical solution for the healthcare industry undergoing digital transformation. This architecture adopts a "never trust, always verify" article that fundamentally differs from traditional perimeter-based security models, making it particularly valuable in healthcare environments where diverse stakeholders require varying access to sensitive data. The implementation of Zero Trust SD-WAN delivers multiple benefits for healthcare organizations, including enhanced security through identity verification, continuous authentication, encrypted data transmission, and comprehensive audit trails. Beyond security, it optimizes network performance through dynamic path selection, quality of service controls, and cloud connectivity optimization—essential for supporting critical applications like telemedicine and electronic health records. While implementation challenges exist, particularly regarding legacy medical device compatibility and balancing security with clinical workflows, properly executed Zero Trust frameworks significantly reduce security incidents and improve regulatory compliance. As healthcare evolves with increasing IoMT adoption, AI integration, and distributed care delivery models, Zero Trust SD-WAN will play an increasingly important role in enabling secure innovation.